The Success of Implementation Inclusive Education Management As A Mirror of the Principal’s Strategy in Realisation of Disability-Friendly Education - Catur Nur Cahyaning; Achmad Supriyanto; Sunarni Sunarni; Catur Nur Cahyaning; Achmad Supriyanto (Universitas Negeri Malang, 2023)
This study aims to describe the successful implementation of inclusive education management as a reflection of the principal's strategy in realizing disability-friendly education. This research uses a qualitative method of case study type. The location of this research at SMAN 1 Rejotangan Tulungagung. The key informant in this study was the School's Inclusive Program Coordinator. Supporting informants include Curriculum Coordinator, Special Assistance Teachers (GPK) and Children with Special Needs (ABK). Collecting data through by observation interviews and documentation. Data analysis is carried out through the process of data collection, condensation, data presentation and verification or drawing conclusions. The results showed that: 1) the principal in implementing the inclusive education program uses a cooperative-collaborative strategy based on the conditions and needs of the school in carrying out its responsibilities as an inclusive school; 2) the process of implementing an inclusive education program starting from the planning process, to monitoring the ongoing program; 3) implementation of intensive learning for children with special needs (ABK) which is supported by the role of special companion teachers (GPK) in each ABK development as evidence of the implementation of the inclusive education program. Inclusive education is implemented in all countries including Indonesia with the aim of providing optimal education services to all groups equally, including the children with special needs.